Diagnostic utility of rapid tests to detect IgG/IgM antibodies against COVID-19 - Pedro Sánchez Frenes; Dayamí García Torres; María de Jesús Sánchez Bouza; Gippsy Mendoza Cartaya; Mavis Portela Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: Rapid tests for the diagnosis of SARS-CoV-2 are attractive options due to their simplicity, speed and cost-effectiveness; but they have different degrees of sensitivity and diagnostic specificity. Objective: to evaluate the analytical performance of rapid tests to detect IgG/IgM antibodies against COVID-19. Methods: descriptive study, carried out with patients admitted to the Héroes de Playa Girón Specialized Ambulatory Center, in Cienfuegos, with a presumptive, probable or confirmed diagnosis of COVID-19 during two periods of time. All of them underwent a rapid test to detect anti-COVID-19 antibodies, in addition to a confirmatory molecular biology test. Diagnostic sensitivity and specificity, predictive values, and rapid test efficiency were calculated within a 95% confidence interval. Results: excellent specificity (98.75%) and regular sensitivity (54.54%) were obtained, as well as good predictive values and overall diagnostic efficiency. Conclusion: The rapid anti-COVID-19 tests evaluated showed adequate diagnostic performance. They constitute an affordable and valuable diagnostic alternative to assess previous exposure to SARS-CoV-2. Its clinical use is restricted to certain medical situations; however, they constitute a useful epidemiological tool.